PP.84 The Impact of Maternal Age and Chorionicity on Obstetric Outcome in Twin Pregnancy. (26th April 2013) - Mahoney, AM O'; Meaney, S; Donoghue, K O'
Abstract : Introduction: The number of twins born in Ireland has increased from 11.8 sets per 1, 000 live births in 1988 to 17.9 in 2011. This study aims to investigate the impact of advanced maternal age and chorionicity on obstetric outcome in twin pregnancies. Methods: A retrospective cohort study of all twin pregnancies delivered from 2009 to 2011 in a large, tertiary hospital (∼8, 000 deliveries per annum) in the Republic of Ireland was conducted. Birth registers and clinic records were reviewed to examine obstetric outcomes. Results: Of the 523 twin pregnancies included in the study 9.6% (n = 50) of mothers were ≥40 years and 47.5% (n = 247) were nulliparous. Advanced maternal age, mother aged ≥40 years, was associated with increased ART (52% vs. 25.2%; p < 0.001) and increased caesarean delivery (78.0% vs. 60.9%; p < 0.001). Differences between the age groups were noted for GDM (9.8% vs. 3.1%; p = 0.007) and PET/PIH (30.8% vs. 13.8%; p < 0.001). 16.3% (n = 87) of twins were monochorionic who had a higher incidence of PTD (65.1% V 47.9%, p = <0.001) and iatrogenic reasons for PTD (69.4% V 52.4%, p = 0.006) than dichorionic twins. Conclusion: As a greater number of women are delaying childbearing, and with advances in ART, there are considerable more first time births, including sets of twins, to older women. The findings of this study indicate that advanced maternal age and nulliparity were associated with adverse obstetric outcome in twin pregnancies.